GSK3‐activated STAT5 regulates expression of SFRPs to modulate adipogenesis. Issue 9 (26th March 2018) - Wang, Li; Wang, Yuan; Meng, Yuan; Zhang, Chao; Di, Lijun
ABSTRACT: Adipogenesis is a tightly regulated cellular process and is closely associated with obesity and its associated metabolic disorders, such as diabetes. Multiple transcription factors and signaling pathways are involved in the regulation of adipogenesis. Here, we report that glycogen synthase kinase (GSK3), which was reported to play an important role in many cellular processes, is essential to adipocyte differentiation at early and terminal differentiation phases. Mechanistically, GSK3 modulates adipogenesis through regulation of both canonical Wnt pathways, which involve Wnt/β‐catenin signaling, and noncanonical Wnt pathways, which include JNK and Ras‐related C3 botulinum toxin substrate signaling. GSK3‐regulated adipogenesis is also mediated by secreted frizzled‐related proteins (SFRPs), especially SFRP1, the canonical Wnt antagonist. The obesity‐induced increase of Sfrp1 expression can be reversed by the GSK3 inhibitor. GSK3‐regulated expression of Sfrp is mediated by signal transducer and activator of transcription 5 (STAT5). We demonstrated that GSK3 activates STAT5 through regulation of its phosphorylation to bind to the promoter of Sfrp genes and the peroxisome proliferator‐activated receptor ? gene to stimulate their expression, which could ultimately lead to a modulated adipogenic process. Our findings identify a GSK3/STAT5/SFRP/Wnt regulatory axis of adipogenesis and shed light on the molecular mechanism of adipogenesis by suggesting that different pathways and adipogenic regulators coordinately modulate adipocyte differentiation.—Wang L., Wang, Y., Meng, Y., Zhang, C., Di, L. GSK3‐activated STAT5 regulates expression of SFRPs to modulate adipogenesis. FASEB J. 32, 4714–4726 (2018). www.fasebj.org